“Robin Hood Where Art Thou?” An Exploratory Multiple Case Studies of Macro and Micro Perspective of Symbiotic Relationship in CSR - Ishak, Ali Yasak (2012)
This dissertation is inspired by the legend of Robin Hood, a character which is synonymous to Nottingham; on his benevolent act to overcome socio-economic imbalance in the past. Up to recently socio economic imbalance is still an issue at stake, as evidenced by the ongoing social unrest in several countries including the developed one. In present day the benevolent act takes a form of Corporate Social Responsibility. At the core of this dissertation are Tabung Haji or the Hajj Funds (TH), KFC Holdings Berhad (KFC) and KPJ Healthcare Berhad (KPJ), Malaysian grown organisations which the author chose as the basis of the study. Through this dissertation the author attempts to document and analyze a pattern of relationship that exists between the selected organisations and their networks. The state of past and present business affairs of CSR pros and cons dominates the dialogue in the literature review; unlike the common approach which usually favours the proponent, the author is of the opinion that both views should be equally embraced for each has its valid and legitimate rationale. A synthesis that follows identified “Symbiosis” as a factor that presents as an imminent gap in the literature review resulting in two themes emerged, and there are “Harmonisation” and “Equilibrium”. Subsequently, a conceptual framework known as Macro and Micro Perspective of Symbiotic Relationship in CSR is proposed; where the Macro Perspective is based on Institutional Theory and deals with the external perception i.e. Organisation’s legitimacy/license to operate, while the Micro Perspective is based on the Network Perspective and deals with specific interaction that takes place between the organisation and its network. The Research Methodology takes a form of exploratory multiple case studies based on qualitative research. In this study, secondary data is considered as primary data. Limitations in research are foreseen based accessibility in relations to information and generalizability over the findings. In this exploratory multiple case studies the findings show that there is a pattern of symbiotic relationship in CSR between organisation and its network, where elements that contribute to harmonisation and equilibrium were identified across the three chosen organisations.